Effect of taurine in muscle damage markers and inflammatory cytokines in running exercise - Wang, Yucong; Xu, Tao; Zhao, Hui; Gu, Chunxiao; Li, Zhongzheng (Frontiers in Physiology, 2022)
This study aimed to investigate the effect of taurine on muscle damage markers and inflammatory markers in the running. For that, ten healthy volunteers participated in this study (mean ± SEM; age 24 ± 1 year, body mass 72.2 ± 4.89 kg, height 174.03 ± 2.85 cm, and BMI 23.83 ± 1.27). The running exercise was performed for 5 km, and blood was taken pre-exercise and pre-exercise + tau and post-exercise and post-exercise + tau for biochemical assessment. We assessed serum creatine kinase (CK), CK isoenzyme, Lactate dehydrogenase (LDH), aspartate transaminase (AST), tumor necrosis factor-alpha (TNF-alpha), and interleukin-6 (IL-6). CK level was not significantly different in the control and taurine (tau) administrated groups. However, creatine kinase isoenzyme was decreased in the pre-exercise + tau group when compared to the post-exercise + tau group. AST level was increased significantly in the post-exercise compared to the post-exercise + tau group. There was no significant difference observed in the LDH level in both post-exercise and post-exercise + tau. TNF-alpha level was not also significantly different in both post-exercise and post-exercise + tau. However, IL-6 was decreased in the post-exercise + tau when compared to the post-exercise group. In conclusion, we observed that taurine decreases the inflammatory response by decreasing IL-6 and AST, suggesting the role of taurine in regulating inflammatory response could help to increase running performance.